Peran Harga, Variasi Produk, dan Brand Image Terhadap Keputusan Pembelian Ulang - Intan Maitri; Ni Wayan Ekawati; Gede Bayu Rahanatha; I Gst. A. Kt. Gd. Suasana (Universitas 45 Surabaya, 2025)
The Paradisein is a brand based in West Denpasar, Bali, that has been producing women’s clothing since 2019 and selling its products online through Shopee e-commerce and Instagram. This study aims to analyze the influence of price, product variety, and brand image on repurchase decisions. The population defined for the research comprises The Paradisein’s customers who have made a minimum of two purchases (repurchase buying). A total of 53 customers met the population criteria. The data analysis techniques used in this study include Validity Tests, Reliability Tests, Classical Assumption Tests, Multiple Linear Regression Analysis, F-tests, and t-tests. The results show that price has a positive and significant influence on repurchase decisions, product variety has a positive and significant influence on repurchase decisions, and brand image also has a positive and significant influence on repurchase decisions. Recommendations for The Paradisein include evaluating the benefits of its products before setting prices to align pricing policies with product value. Additionally, it is suggested to diversify raw materials to enhance the quality variety of materials used. Regular social media promotions and market research are also recommended to improve company performance.